Zinc application in seeds and its effect on germination, nutrition and initial development of sorghum - Yagi, Renato; Simili, Flávia Fernanda; Araújo, João Carlos de; Prado, Renato de Mello; Sanchez, Sérgio Veraguas; Ribeiro, Carlos Eduardo Rodrigues; Barreto, Vitor Corrêa de Mattos (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to evaluate the effect of zinc application in sorghum seeds (Sorghum bicolor (L.) Moench) on its nutrition, germination and on the initial development of the plants in greenhouse. A completely randomized design of the treatments was used, in the factorial scheme 2x5, with two cultivars of sorghum (BR 304 and BR 310) and five rates of Zn (0, 3.57, 7.14, 14.28 and 28.56 g of Zn per kg of seeds), with three replicates. The variables of germination (average time, daily average and the speed) were evaluated, and 28 days after sowing dry matter and Zn levels in the aerial part and roots were determined. The Zn application in sorghum seeds did not affect the accumulation of dry matter aerial part, however, it decreased the germination and the accumulation of roots and whole plant dry matter. The Zn applied in sorghum seeds accumulated mainly in the roots. The cultivar BR 304 showed higher Zn absorption and dry matter accumulation than the cultivar BR 310.